Determination of ideal target exercise heart rate for cardiac patients suitable for rehabilitation. Issue 11 (6th July 2017) - Tan, Shih Jia Janice; Allen, John Carson; Tan, Swee Yaw
Abstract : Background: Exercise prescription for patients with cardiovascular disease remains a challenge. The concept of exercising at an intensity equivalent to one's anaerobic threshold has been well studied and highly recommended in the fitness industry for other populations. For this concept to be applicable to patients with cardiovascular disease, the level and intensity of activity must not trigger myocardial ischemia. Hypothesis: We hypothesized that the heart rate at ventilatory anaerobic threshold (HRVAT ) will not exceed heart rate at ischemic threshold (HRIT ) (ie, HRVAT ≤ HRIT in a majority [>50%] of patients). Methods: In this retrospective pilot study, 19 patients, mean age at baseline of 45.0 ± 15.6 years, who had positive cardiopulmonary exercise stress testing were included. Heart rate at ventilatory anaerobic threshold (VAT) was derived from a computer‐analyzed V‐slope method. The ischemic threshold (IT) was determined from electrocardiogram. The exercise test parameters at VAT in relation to IT were examined. Results: Heart rate at VAT preceded heart rate at IT in 89.5% of patients. On average, achievement of VAT preceded IT relative to workload (119.5 ± 49.6 vs 132.6 ± 47.5; P < 0.01), heart rate (121.2 ± 15.9 vs 133.3 ± 17.5; P < 0.01), oxygen consumption (19.3 ± 4.9 vs 20.8 ± 3.7; P < 0.01), and respiratory exchange ratio (0.96 ± 0.10 vs 1.01 ± 0.07; P < 0.01). Conclusions: Greater than 50% of patients met the criteria of HRVAT ≤ HRIT ; therefore, we propose that anaerobic threshold is a suitable target aerobic exercise heart rate for all patients with cardiovascular diseases indicated for cardiopulmonary rehabilitation.